STUDY OF HANDLING LAND ACQUISITION PROBLEMS ON THE YOGYAKARTA – BAWEN TOLL ROAD PROJECT SECTION 1 - Anggun Primadhani; Suhariyanto Suhariyanto (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
The Yogyakarta–Bawen Toll Road Project Package 1, Section 1, is a government-initiated infrastructure development project aimed at enhancing regional economic growth and connectivity in the southern part of Java. However, the construction progress of the toll road, particularly at the at-grade section STA 75+150 – 75+250, has been delayed due to unresolved land acquisition issues. Therefore, a study on handling land acquisition problems for the Yogyakarta–Bawen Toll Road Project Section 1 is essential to ensure the project proceeds as planned. This study aims to address the land acquisition issue by proposing alternatives, such as realigning the road (trace) or constructing a bridge. The research involves designing basic alternatives for both the new road alignment and the bridge, followed by an analysis to determine the most effective and optimal solution. The steps taken include proposing a new road alignment, designing a bridge, estimating the construction time and cost for each alternative, and selecting the most efficient option. The study’s result show that the proposed new road alignment is located to the south of the current toll road construction, while the bridge design remains on the original alignment with a specific elevation adjustment. The estimated implementation time and cost for the new road alignment are 228.5 working days and IDR 87,907,195,901.12, respectively, whereas for the bridge, they are 249.5 working days and IDR 84,694,979,884.13. Based on these findings, it can be concluded that road realignment is the more effective and optimal solution.